The Correlation of Social Support through the Quality of Life of Menopausal Women at Puskesmas Kelurahan Pondok Bambu II, Duren Sawit District, East Jakarta in 2021 - Heriza Syam; Andini Fitriani; Wa Ode Hajrah; Siti Masitoh; Jehanara Jehanara (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The increase in life expectancy in Indonesia has implications for the increase in the population of postmenopausal women. Menopausal women experience hormone deficiencies that cause complaints of vaginal atrophy, hot fluses, weight gain, bone pain, depression and others, which affect women's quality of life. This is supported by the results of research by Ruri Yuni, et al (2014) which states that 69.6% of menopausal women's quality of life is affected by menopausal syndrome. The purpose of the research: to determine the correlation of social support to the quality of life of women in dealing with menopausal life in the Puskesmas Pondok Bambu II Village. Research method: quantitative, with a cross sectional analytic design. The sample of this study was 45-55 years old postmenopausal women who had a family/husband in Puskesmas Kelurahan Pondok Bambu II area are 47 people. This research uses Purposive Sampling Technique. The results: from 47 respondents, menopausal women with social support with good quality of life were 20 respondents (76.9%), compared to menopausal women who received social support but had poor quality of life by 6 respondents (23.1%). The results of the Chi-Square test obtained p value of 0.003 which means that there is a relationship between social support and the quality of postmenopausal women.Conclusion Our study confirms the differences Quality of life of postmenopausal women between social support and non-social support. The impact of educational level, occupation and income and knowledge about menopause as predictors of a better quality of life in postmenopausal women.